The problems of collective action: A new approach - Katharina Holzinger (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2003)
The problem of collective action is usually identified with social dilemmas. A wider notion of the term collective action problem is introduced, as dilemmas are not the only problems to arise in collective action. The article first presents a typology of collective action problems based on matrix game analysis. Five types are distinguished: distribution, defection, co-ordination, disagreement, and instability problems. Second, the article discusses a number of proposals how to resolve these types of collective action problems, such as altruism, norms, focal points, correlated strategies, collective decision-making, external power, and sanctioning. Whereas the political solutions can be used to resolve all types of problems, the motivational solutions can only facilitate the resolution of some of the problems, and the rational expectation solutions can solve some types and help to solve others.
Keywords: 330; Neue politische Ökonomie; Spieltheorie; Gefangenendilemma; Theorie